Mental health status and its associated factors among female nurses in the normalization of COVID-19 epidemic prevention and control in China - Mao, Xiaofei; Dong, Wei; Zhang, Jianguo; Zhang, Fan; Deng, Wenxi; Li, Ziqiang; Hou, Tianya (Frontiers in Public Health, 2023)
【Abstract】Objective: To investigate mental health status and its associated factors among female nurses in the normalisation of COVID-19 epidemic prevention and control in China. Methods: Random cluster sampling was applied to recruit 740 female nurses in China. The respondents completed the survey with mobile devices. Demographic questionnaire, Generalized Anxiety Disorder-7, Patient Health Questionnaire-9, Insomnia Severity Index, and The Impact of Event Scale-Revised were used to assess demographic Information, anxiety, depression, insomnia and PTSD symptoms, respectively. The associated factors of mental health status were identified by binary logistic regression analysis. Results: The prevalence of anxiety and depression was 7.9% and 17.8%, respectively. Insomnia was an associated factor of anxiety (OR=6.237, 95%CI=6.055-23.761, P<0.001) and depression (OR=9.651, 95%CI=5.699-22.370, P<0.001), while PTSD was an associated factor of anxiety(OR=11.995, 95%CI=2.946-13.205, P<0.001) and depression (OR=11.291, 95%CI=6.056-15.380, P<0.001), Being married was a protective factor of depression(OR=0.811, 95%CI=1.309-6.039, P<0.01). Conclusion: Female nurses showed problems in mental health. Insomnia, PTSD and marital status were associated with mental health. The hospital management should pay more attention to the unmarried groups, and strive to improve the sleep quality of female nurses and reduce their stress caused by traumatic events.